REMOVAL OF IMPURITIES FROM THE GAS PHASE OF HIGH -TEMPERATURE REACTION ZONE OF THE LIQUID STEEL-MELTING BATH - Kharchenko , Аlеxander; Sinyakov , Ruslan; Lichkonenko, Natalia (Scientific Journal "Metallurgy", 2020)
Removal of impurities from the gas phase of a liquid steelmaking bath is an important process in which the chemical elements irrevocably leave the room of the steelmaking unit. For the sake of efficient control of the heat technological parameters, there is a need to study this process in detail when blowing a liquid ironcarbon melt with an oxygen. The paper studies the behavior of iron and impurities of carbon, oxygen, silicon, manganese, aluminum, sulfur, phosphorus, calcium and magnesium in the gas phase of the hightemperature reaction zone (HRZ) of a liquid steel bath when it is purged with oxygen, taking into account the influence of all components of the thermodynamic system “metal-slag-gas". It has been shown that as the blowing intensity and bath temperature increase, the concentration of a number of impurities in the gas phase of the secondary flow passes through a maximum at a certain temperature, which depends on the blowing intensity, after which intensive removal of this impurity from the steelmaking bath begins. In absolute units, with an increase in temperature, the passage of this impurity into the gas phase does not decrease, and in the general case, maxima are not observed. According to the temperature and the degree of removal into the gas phase, the studied impurities can be divided into three groups: a) carbon, which is completely removed at a relatively low total oxygen content in the HRZ and temperatures up to 2000°C; b) silicon, calcium, magnesium and phosphorus, which are almost completely removed into the gas phase in the temperature range 2100...2800°C; c) manganese, sulfur, iron and aluminum, which are partially removed at temperatures above 2600°C. With an increase in the total oxygen content in the SEC over 15%, the temperature increase sharply slows down, reaching the limit of 2900°C with a total oxygen content of 20%. In this case, iron intensively enters the gas phase along with impurities. In addition, a significant amount of slag is formed, consisting mainly of iron oxides. Therefore, purging the steelmaking bath with oxygen with an intensity of more than 5 m3 / (t • min) is impractical, since it does not significantly increase the productivity of the steelmaking unit.